2019
DOI: 10.1155/2019/8640549
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of Early-Stage Glottic Laryngeal Carcinoma Patients Treated with Radical Radiotherapy Using Different Techniques

Abstract: Purpose The aim was to evaluate the treatment outcomes and prognostic characteristics of patients with early-stage glottic laryngeal carcinoma who underwent radical radiotherapy (RT) with different techniques. Patients and Methods Radiotherapy was applied using the 2D conventional technique between 1991 and 2004 (130 patients), 3DCRT until 2014 (125 patients), and by VMAT until January 2017 (44 patients). Clinical T stages were 38 (12.7%) for Tis, 209 (69.9%) for T1, and 52 (17.4%) for T2. Radiotherapy techniq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 39 publications
1
7
0
Order By: Relevance
“…Some studies have reported five-year laryngectomy-free survival rates at 80-86% for T2 stage cancers after RT. 11,12 Studies have reported various rates of dysfunctional larynges after radiation ranging from 0.3-21% although stratification of cancer stage was not specified in any of the studies. 9,11,12 Allen et al reviewed several studies which showed that 45%-75% of those with post-radiation changes were found to have recurrent or residual malignancy.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have reported five-year laryngectomy-free survival rates at 80-86% for T2 stage cancers after RT. 11,12 Studies have reported various rates of dysfunctional larynges after radiation ranging from 0.3-21% although stratification of cancer stage was not specified in any of the studies. 9,11,12 Allen et al reviewed several studies which showed that 45%-75% of those with post-radiation changes were found to have recurrent or residual malignancy.…”
Section: Discussionmentioning
confidence: 99%
“…There was a trend for increased local recurrences in the T2 N0 population, which highlighted the potential consequences for not adequately appreciating the risk of local subclinical spread above or below the glottis. Although follow-up periods are short, the dosimetric advantages to OARs and comparable local control rates for IMRT and VMAT have been further demonstrated by numerous retrospective analyses (11,(103)(104)(105)(106)(107).…”
Section: Radiotherapy Technique and Outcomesmentioning
confidence: 99%
“…Spread beyond the vocal cord frequently occurs through invasion of the anterior commissure, as the attachment of Broyles’ ligament onto the thyroid cartilage serves as a weak point, where tumour may invade through the cricothyroid membrane into the laryngeal cartilage and supraglottic or subglottic spaces ( 10 ). Anterior commissure invasion appears to be the most important prognostic determinant for local control for ESGC ( 11 ).…”
Section: Patterns Of Disease Spreadmentioning
confidence: 99%
“…At present, clinical strategies for treating LC include surgery, radiotherapy, chemotherapy and systemic treatment (5)(6)(7)(8). Early treatment has achieved good results with the 5-year disease-specific survival > 75% (9)(10)(11). For patients with advanced LC, total laryngectomy may be the only option (5,12); however, problems caused by this surgery (such as loss of speech and swallowing dysfunction) greatly reduce patient quality of life.…”
Section: R I P T Introductionmentioning
confidence: 99%